Leveraging social science research to combat poverty and inequality in the Middle East - a pathway to achieving SDGs 1 and 10 - Chadi Azmeh; Hiba Darwich (Cogent Social Sciences)
This study examines the relationship between the output of social sciences research, which is measured in terms of both quantity and quality, and two important Sustainable Development Goals (SDG) 1 and 10: poverty and inequality. The study analyzes data from 15 Middle Eastern countries from 2000 to 2023 using a panel regression model based on Panel-Corrected Standard Errors (PCSE) and Feasible Generalized Least Squares (FGLS) techniques. The study findings indicate that while both dimensions of research output exert a notable impact on poverty reduction, the quality of social science research emerges as a more potent catalyst than quantity in formulating effective interventions against poverty. Conversely, both the quantity and quality of research output exhibit comparable effects on the reduction of inequality. These findings underscore the necessity for policymakers to prioritize not just the quantity of research but also its quality, particularly in the quest to combat poverty. Our study advocates for a paradigm shift in policy approaches, emphasizing the urgent need for investment in high-quality research to enhance sustainable socio-economic development in the MENA region. This strategic focus is imperative for tackling the complex challenges of poverty and inequality, ultimately advancing social equity and fostering sustainable economic growth.